Queensferry Crossing, UK: project scope and development history. Issue 2 (17th April 2018) - Shackman, Lawrence; Glover, Mike; Murray, Iain; Hunter, Stuart
Abstract : The Forth Road Bridge has carried road traffic across the Forth estuary in Scotland, UK, since 1964. It was replaced in September 2017 by the Queensferry Crossing, the country's biggest infrastructure project in a generation. The outturn £1·34 billion replacement crossing project consists of a 2·7 km long cable-stayed bridge, associated connecting roads and junction improvements and a state-of-the art 22 km long intelligent transport system to manage traffic through the project corridor. This paper describes the project history, its development and scope.